Prevalence of anxiety and depression among pregnant women during the COVID-19 pandemic: a meta-analysis - Masumeh Ghazanfarpour; Fereshteh Bahrami; Farzaneh Rashidi Fakari; Farzane Ashrafinia; Masoudeh Babakhanian; Mohammad Dordeh; Fatemeh Abdi (Taylor & Francis Group, 2022)
Purpose Coronavirus disease (COVID-19) is a newly emerged respiratory illness, which has spread around the world. Pregnant women are exposed to additional pressure due to the indirect adverse effects of this pandemic on their physical and mental health. Since the psychological wellness framework is weak in developing countries, it is likely that geographical factors affect the prevalence. Therefore, the goal of this meta-analysis is to investigate the prevalence of anxiety and depression among pregnant women during the COVID-19 pandemic. Methods We searched databases including PubMed/MEDLINE, Web of Science, Cochrane Library for articles. The quality of studies was determined based on the STROBE checklist. I2 and Cochrane Q-test were used to determine heterogeneity. Fixed effects and/or random effects models were also employed to estimate pooled prevalence. Results Since heterogeneity was fairly high in all analyses, the random effect model was used. According to the results of random effects in the meta-analysis, the pooled prevalence was 18.7% (95% CI: 0.06-0.36%; ) for anxiety and 25.1% (95% CI: 0.18-0.33%; ) for depression. The results of continent subgroup analysis showed that the prevalence of anxiety was higher in western country (38%) than in Asia country (7.8%). The prevalence of anxiety in Italy (38%), Canada (56%), Pakistan (14%), Greece (53%), Sri Lanka (17.5%), and China (0.3-29%) and Iran 3.8% as well as the prevalence of depression in Canada (37%), Belgium (25%), Turkey (35.4%), Sri Lanka (19.5%), and China (11-29%) has been reported. Conclusion Covid-19 may impose extra pressure on the emotional wellbeing of pregnant women. Therefore, there is an urgent need for resources to help mitigate anxiety and depression in pregnant women.